Effect of initial low oxygen stress combined with 1-methylcyclopropene in ’Royal Gala’ apple quality stored under ultralow O2 - Brackmann, Auri; Anese, Rogério Oliveira; Weber, Anderson; Both, Vanderlei; Gasperin, Adriano Roque de; Pavanello, Elizandra Pivotto (Semina: Ciências Agrárias, 2013)
The aim of this study was evaluated initial low oxygen stress (ILOS) and the interaction with 1-methylcyclopropene (1-MCP) during ultralow oxygen (ULO) storage in maintenance of 'Royal Gala' apple quality. The experiment was conducted in a completely randomized design, with two-factor. Each ILOS was applied for 14 days with 0.4 kPa O2. The treatments evaluated were: [1] 1.2 kPa O2 + 2.0 kPa CO2 (control); [2] 0.6 kPa O2 + 1.0 kPa CO2 (without stress); [3] 0.6 kPa O2 + 1.0 kPa CO2 (one stress); [4] 0.8 kPa O2 + 1.0 kPa CO2 (one stress); [5] 0.6 kPa O2 + 1.0 kPa CO2 (two stresses); [6] 0.6 kPa O2 + 1.0 kPa CO2 (three stresses). The fruits were kept at 0.5 ºC (Â±0.1) and relative humidity of 97% (Â±2.0). After seven months of storage plus seven days of self-life at 20 ºC, the following variables were assessed: internal breakdown, mealiness, crack, healthy fruits, flesh firmness, decay, ethylene production, ACC (1-aminocyclopropane-1-carboxylic acid) oxidase activity and respiration. ILOS and ULO do not decrease internal breakdown, mealiness and crack. ILOS associated to ULO, with or without 1-MCP, is not efficient in maintaining quality and reduce physiological disorders during 'Royal Gala' apple storage harvested at advanced maturity stage, besides induce more decay.